2016
DOI: 10.1074/jbc.m116.745935
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein Convertase Processing Enhances Peroxidasin Activity to Reinforce Collagen IV

Abstract: Edited by Amanda FosangThe basement membrane (BM) is a form of extracellular matrix that underlies cell layers in nearly all animal tissues. Type IV collagen, a major constituent of BMs, is critical for tissue development and architecture. The enzyme peroxidasin (Pxdn), an extracellular matrix-associated protein, catalyzes the formation of structurally reinforcing sulfilimine cross-links within the collagen IV network, an event essential to basement membrane integrity. Although the catalytic function of Pxdn i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…This was confirmed in a recent study that showed the cleavage of trimeric hsPxd01 at Arg 1336 C-terminal of the peroxidase domain by a proprotein convertase (8). The truncation eliminates the von Willebrand factor and renders the peroxidase more active.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…This was confirmed in a recent study that showed the cleavage of trimeric hsPxd01 at Arg 1336 C-terminal of the peroxidase domain by a proprotein convertase (8). The truncation eliminates the von Willebrand factor and renders the peroxidase more active.…”
Section: Introductionsupporting
confidence: 63%
“…However, elimination of the LRR and VWC domains increased the activity of the respective recombinant construct (5). Recently, Colon and Bhave (8) demonstrated that proprotein convertase processing enhances peroxidasin 1 activity by elimination of the VWC domains and proposed that this event represents a key step in the biosynthesis and function of hsPxd01 to support basic membrane and tissue integrity. These findings motivated us to design several constructs, including the POX domain only to search for a functional and well folded protein for first comprehensive pre-steady-state kinetic studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition experiments with aprotinin, PMSF, and Dec-RVKR-CMK indicated that a serine protease is likely to be responsible for the proteolytic processing of LOXL2. Interestingly, it has recently been shown that a proprotein convertase (PC) activates peroxidasin, the enzyme responsible the forma-tion of sulfilimine crosslinks in the C-terminal noncollagenous domain (NC1) of collagen IV (36). Although the blockade of LOXL2 proteolytic processing by Dec-RVKR-CMK inhibitor suggested the involvement of a PC, this family of proteases has a strong preference for Arg in P1 in the motif R-X-R/K-R.…”
Section: Loxl2 Processing and Collagen IV Crosslinking Loxl2 Processimentioning
confidence: 99%
“…The catalytic efficiency is increased with a truncated PXDN construct containing only the Ig and heme peroxidase domains (94,126), suggesting that the LRR and/ or the vWFC domains may ''auto-inhibit'' catalytic activity. Indeed, proprotein convertase processing of PXDN with resulting loss of the vWFC domain enhances PXDN-mediated HOBr generation (20). Whether proteolytic processing or conformational changes involving the LRR domain also activate PXDN is unknown.…”
Section: Anabolic Role Of Hobr In Bm Assemblymentioning
confidence: 99%